Effects of computer assisted instruction on senior secondary school students’ achievement learning outcome in chemistry in Osun State (2010)
This study determined the effects of computer assisted instruction on senior secondary school students’ academic achievement in chemistry in Osun State. The moderating effect of students’ gender and attitude on students’ achievement was also examined. The study adopted one group pretest-posttest experimental research design. Three secondary schools provided with computer tablets by the state government of Osun were purposively selected for the study. Chemistry class was randomly selected in each of the three schools making a total of 152 students (male and female) participated in the study. Students pre and post-test Chemistry achievement scores and Students Attitude Questionnaire on Minicomputer Tablet (SAQMT) were used to collect data. Data were analyzed using Analysis of Covariance (ANCOVA). Five hypotheses were tested at 0.05 level of significance. Results showed that Computer Assisted Instruction has no effect on students’ academic achievement in Chemistry (F(1,151) = 2.129; P > 0.05). It was also revealed that gender and attitude have no effect on students’ achievement in Chemistry. The study therefore recommends that necessary skills in the use of computer tablet for teachers and students, which will assist teaching and learning with computer for students’ achievement.